1983
DOI: 10.1172/jci110911
|View full text |Cite
|
Sign up to set email alerts
|

Effects of free fatty acid availability, glucagon excess, and insulin deficiency on ketone body production in postabsorptive man.

Abstract: A B S T R A C T The present studies were undertaken to assess the relative effects of free fatty acid (FFA) availability, glucagon excess, and insulin deficiency on ketone body (KB) production in man. To determine whether an increase in FFA availability would augment KB production in the absence of insulin deficiency and glucagon excess, plasma insulin and glucagon were maintained at basal concentrations by infusion of somatostatin and exogenous insulin and glucagon, and plasma FFA were increased from 0.32±0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
62
1
3

Year Published

1985
1985
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(71 citation statements)
references
References 37 publications
(62 reference statements)
5
62
1
3
Order By: Relevance
“…The M value, clamp glucose oxidation, and clamp glucose storage were negatively correlated with obesity expressed as percent body fat (fat mass/total weight) or body mass index (BMI) (27,42,43), and liver ketogenesis (44). In discussing that energy balance is confined to much narrower limits than metabolism of FFAs it should be noted that FFA metabis the oxidation of carbohydrate or lipid.…”
Section: Methodsmentioning
confidence: 99%
“…The M value, clamp glucose oxidation, and clamp glucose storage were negatively correlated with obesity expressed as percent body fat (fat mass/total weight) or body mass index (BMI) (27,42,43), and liver ketogenesis (44). In discussing that energy balance is confined to much narrower limits than metabolism of FFAs it should be noted that FFA metabis the oxidation of carbohydrate or lipid.…”
Section: Methodsmentioning
confidence: 99%
“…To our knowledge, rates of ketogenesis have not been measured in hyperosmolar nonketotic patients using either organ balance or isotopic methods. Subsequent work using tracer methods (41,74) has demonstrated that even brief withdrawal of insulin from type 1 diabetic patients results in prompt development of ketosis. Insulin withdrawal from diabetic patients, however, leads to complex changes in circulating concentrations of many stress hormones.…”
Section: Lipid and Ketone Metabolismmentioning
confidence: 99%
“…Plasma concentrations of IL-6 and TNF-␣ were measured by Quantine High Sensitivity kits (R & D Systems, Minneapolis, MN). Plasma fatty acid and triglyceride concentrations were determined by using a microfluorimetric method (39).…”
Section: Proton Mrs Of Intramyocellular Triglyceride and Htg Contentmentioning
confidence: 99%